(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
The article analyzes the right to health of a person, including children and women, on the basis of universal international legal documents and national legal documents. The role of the right to health care in the human rights system is highlighted, and based on these analyzes, views on the modern understanding of the right to health are presented. Conclusions and recommendations have been put forward based on the analysis of issues related to the provision of a person’s right to health.